Power Quality Ｒemote Monitoring System Design - XUE Ping; WANG Ya-bin; WANG Yu; ZOU Xue-zhou; YAO Juan (Journal of Harbin University of Science and Technology)
This paper designed the power quality remote monitoring system based on FPGA. The system uses hardware phase-locked frequency tracking technology for Synchronous sampling of the three-phase voltage，current， reducing leakage and spectral interference between spectrums. This system uses FPGA＇s FFT IP core to complete 256 points of the harmonic operation and uses SOPC and Nios II soft-core embedded processor to read data collected and harmonic operation results，combining with Marvell88E1111 network chip to transmit data to the host computer. The host computer process and data further，thus achieving power quality parameters for remote monitoring purposes.